Staff understanding of recovery-orientated mental health practice: a systematic review and narrative synthesis - Le Boutillier, Clair; Chevalier, Agnes; Lawrence, Vanessa; Leamy, Mary; Bird, Victoria; Macpherson, Rob; Williams, Julie; Slade, Mike (BioMed Central, 2015)
Background: Mental health policy is for staff to transform their practice towards a recovery orientation. Staff understanding of recovery-orientated practice will influence the implementation of this policy. The aim of this study was to conduct a systematic review and narrative synthesis of empirical studies identifying clinician and manager conceptualisations of recovery-orientated practice.